Prevalence of bovine aortic arch variant in patients with aortic dissection and its implications in the outcome of patients with acute type B aortic dissection - Mylonas, Spyridon; Ante, Marius; Böckler, Dittmar (European journal of vascular and endovascular surgery, 2018)
Objective/Background - To investigate the prevalence of bovine arch (BA) among patients with type A and B aortic dissection, and to provide insight into the implication of this variation on the outcome of patients with acute or subacute type B aortic dissection (a/sTBAD). - Methods - This retrospective cohort analysis includes patients with a/sTBAD admitted between January 2006 and December 2016. Computed tomographic angiograms (CTAs) of patients referred because of type A aortic dissection were also re-evaluated with regard to the presence of BA. As a control group, 110 oncological patients who had undergone a chest CTA for disease staging during the study period were enrolled. A total of 154 patients with a/sTBAD and 168 with type A aortic dissection were identified during the study period. - Results - An overall prevalence of 17.6% for BA variants was revealed. The comparison between patients with aortic dissection and the control group showed no statistically significant difference in BA prevalence (17.7% vs. 17.3%; p = 1.0). No statistically significant difference in BA prevalence was observed when comparing patients with type A aortic dissection with those with type B aortic dissection (16.6% vs. 18.8%; p = .66). During a median follow-up period of 27.8 months, 30 patients died. The mortality rate among patients presenting a BA variant was 34.5%, whereas among patients without, it was 16.0% (p = .04). Multivariate analysis revealed the presence of a BA as an independent predictor of mortality (adjusted odds ratio 3.4, 95% confidence interval 1.2-9.8). - Conclusion - The BA should be considered as a predictor of the outcome for patients with type B aortic dissection.
Gesehen am 04.12.2019
Falsche Schreibweise von Dittmar Böckler in Verfasserangabe der Vorlage